2015
DOI: 10.1016/j.taap.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Human bronchial epithelial BEAS-2B cells, an appropriate in vitro model to study heavy metals induced carcinogenesis

Abstract: Occupational and environmental exposure to arsenic (III) and chromium VI (Cr(VI)) have been confirmed to cause lung cancer. Mechanisms of these metals-induced carcinogenesis are still under investigation. Selection of cell lines to be used is essential for the mechanistic studies. Human bronchial epithelial BEAS-2B cells are the cells to be utilized by most of scientists. However, due to p53 missense mutation (CCG → TCG) at codon 47 and the codon 72 polymorphism (CGC → CCC) in BEAS-2B cells, its usage has freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 41 publications
1
54
0
1
Order By: Relevance
“…We chose this particular model system also because it has been previously shown that environmental exposures can induce cell transformation of these cells (Lu et al 2015; Park et al 2015; Son et al 2012; Vales et al 2015; Zhang et al 2012). The BEAS-2B cells have been used for about 30 years in various biomedical research studies, including toxicological studies that tested chemicals, including organic, inorganic and particular agents (Fuentes-Mattei et al 2010; Garcia-Canton et al 2013; Lansley 2015; Rodrigues et al 2009; Steerenberg et al 1998; Sun et al 1995; Verstraelen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose this particular model system also because it has been previously shown that environmental exposures can induce cell transformation of these cells (Lu et al 2015; Park et al 2015; Son et al 2012; Vales et al 2015; Zhang et al 2012). The BEAS-2B cells have been used for about 30 years in various biomedical research studies, including toxicological studies that tested chemicals, including organic, inorganic and particular agents (Fuentes-Mattei et al 2010; Garcia-Canton et al 2013; Lansley 2015; Rodrigues et al 2009; Steerenberg et al 1998; Sun et al 1995; Verstraelen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, compared with the air-liquid interface cell exposure (ALICE) system, submerged culture system is more suitable for modeling chronic exposure (Herzog et al 2014), as the oil pollutants exposure scenario in our study. We did not use KGM but used DMEM as the culture medium because we carefully followed the culture medium condition (DMEM) that was previously reported for studying exposure-induced malignant transformation of the BEAS-2B cells (Huang et al 2015; Kim et al 2015; Liu et al 2014; Park et al 2015; Son et al 2012; Stueckle et al 2012). In addition, numerous studies (e.g., (Dieudonne et al 2012; Jahn et al 2000; Kaur et al 2008; Skuland et al 2014)) have used BEAS-2B cells cultured in DMEM as a model for airway epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…1 This cell model has been reported as an appropriate model for in vitro lung carcinogenesis studies. 23,24 BSW cells were maintained in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 5% fetal bovine serum (FBS), 2 mM L-glutamine, 100 units/mL penicillin, and 100 μ g/mL streptomycin (Gibco, Gaithersburg, MA). Cells were grown at 37 °C in a humidified 95% air/5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, more attention has been paid to an in vitro model, using BEAS‐2B cells. This cell line is commonly used for exogenous chemical toxicity studies to examine the mechanisms involved in toxicity [13,14] …”
Section: Introductionmentioning
confidence: 99%